Excellent Field‐Emission Performances of Neodymium Hexaboride (NdB6) Nanoneedles with Ultra‐Low Work Functions. (21st August 2013) - Xu, Junqi; Hou, Guanghua; Mori, Takao; Li, Huiqiao; Wang, Yanrui; Chang, Yangyang; Luo, Yongsong; Yu, Benhai; Ma, Ying; Zhai, Tianyou
<x xml:space="preserve">Abstract</x> High‐quality NdB6 nanostructures with a low work function are successfully synthesized via an one‐step catalyst‐free chemical vapor deposition process. Field emission properties of these nanostructures (curve nanowires, short‐straight nanorods, long‐straight nanowires, and nanoneedles) are systematically investigated and found to be strongly affected by the tip morphologies and temperatures. The nanoneedles with sharp tips demonstrate the lowest turn‐on (2.71 V/μm) and threshold (3.60 V/μm) electric fields, as well as a high current density (5.37 mA/cm2) at a field of 4.32 V/μm in comparision with other nanostructures. Furthermore, with an increase in temperature from room temperature to 623 K, the turn‐on field of the nanoneedles decreases from 2.71 to 1.76 V/μm, and the threshold field decreases from 3.60 to 2.57 V/μm. Such excellent performances make NdB6 nanomaterials promising candidates for application in flat panel displays and nanoelectronics building blocks.